Mental health outcomes and rehabilitation challenges in children with orthopedic trauma: a public health survey from a pediatric rehabilitation center - Zheng, Shuyue; Cheng, Lijie; Zhao, Xiaoyu; Fang, Jihong; Li, Dunhui; Wu, Fengqin (Frontiers in Public Health, 2025)
ObjectivesThis study aimed to assess mental health outcomes and rehabilitation challenges among Chinese children with orthopedic trauma and to identify multilevel determinants and causal pathways underlying these outcomes.Materials and methodsA single-center cross-sectional survey, supplemented by a 1-year prospective follow-up, was conducted among children enrolled at Anhui Provincial Children’s Hospital, China. Validated Chinese instruments were used to assess PTSD, depression, anxiety, QoL, persistent pain, sleep disturbance, and social support, along with electronic records of injury and rehabilitation data. Analyses included conventional single-level regression, mediation, moderation models, propensity score matching, and clustering, with all models adjusted for sociodemographic and clinical factors.ResultsAmong 2,103 children with orthopedic trauma, the prevalence of PTSD, depression, and anxiety was not directly reported as percentages; mean scores were 8.4, 12.2, and 4.0, respectively. A total of 26.6% of participants reported persistent pain and sleep disturbance, although data were not explicitly provided. Rural Hukou independently predicted higher PTSD (β = 0.47; 95% CI: −0.08 to 1.01) and lower health-related quality of life (QoL) (β = −0.67; 95% CI: −1.25 to −0.10), even after adjusting for injury severity and income. Higher income was not significantly protective (PTSD β = −0.17; QoL β = −0.02). Acute pain intensity mediated 38.9% of the association between income and depression (indirect β = 0.007; p < 0.001). Social support moderated the relationship between ISS and depression (interaction β = −0.08; p = 0.001). Early rehabilitation (≤14 days) was associated with reduced PTSD (Δ = −0.91; p < 0.001), lower odds of pain (OR = 0.81; p = 0.04), and improved recovery. Cluster analysis identified a rural high-risk subgroup (proportion unknown) with elevated PTSD, pain, and depression, underscoring the need for targeted psychosocial interventions.ConclusionSocioeconomic disadvantage, rural residence, and injury severity jointly worsen psychological outcomes and hinder rehabilitation, highlighting the need for timely rehabilitation and targeted psychosocial support to reduce disparities and promote recovery in pediatric populations in eastern China.